Consumer willingness to pay for domestic water services in Kelantan - Kamaludin, Mahirah; Radam, Alias; Abdul Rahim, Khalid; Yacob, Mohd Rusli (Universiti Putra Malaysia Press, 2013)
The importance of water to life cannot be denied as it is the most precious substance among all our natural resources. Rapid population growth and urbanization have increased the demand for water which is expected to undergo substantial changes in the future. Kelantan faces many problems in the water sector. The state lacks financial resources to improve its water supply coverage. In fact, there are numerous functions which are supported by the price of water itself such as the costs of water treatment, water storage, and delivery to its customers. Low water rates may lead to heavy losses to the water provider who is expected to provide various services to the community, including the delivery of clean and adequate water supply. This study utilizes Contingent Valuation Method (CVM) to derive consumers' willingness to pay (WTP) for improved water services, and based on the WTP value obtained, the aggregate monetary benefits of improving water services for the consumers of Kelantan are estimated. Logit model is used to analyze primary data gathered during the survey. The estimated mean WTP for improved domestic water services is RM0.5979 applicable on the first 35m3 (i.e. 8.7% above the current price). The findings offer policy recommendations to address the numerous, serious water issues faced by the state. The appropriate water tariff may help the water provider to overcome the problems /challenges in providing better services in the state.